Fischler claims that the EU was not responsible for the failure at Cancun - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Speaking in Canada on September 16th 2003 EU Agriculture Commissioner Franz...